Implementation of Discovery Learning to Improve Elemental Chemistry Learning Outcomes of 11th Graders at SMK Negeri 4 Palembang - Tiara Indah Agustinah; Hartono Hartono; Rahman Susanto (Research in Education, Technology, and Multiculture, 2022)
Abstract: This research was conducted with the aim of improving student learning outcomes and learning activities carried out. The research method was conducted in Classroom Action Research (CAR) which was carried out in two cycles, where each cycle consisted of 4 stages of activities namely planning, implementing, observing, and reflecting (reflection). Each cycle is held in two meetings with a time allocation of 2 x 45 minutes per meeting. Based on the research data, it can be seen that there was an increase (1) the learning outcomes experienced by students from cycle I were 57.14% to 91.42% of cycle II. (2) the learning activities of students from cycle I are 53% to 65% in cycle II. Thus it can be concluded that the application of the Discovery Learning Model can improve student learning outcomes and activities in material Chemistry Class XI TGB 2 at SMK Negeri 4 Palembang. Keywords: discovery learning, learning outcomes, classroom action research.